Quality of Care for PTSD and Depression in the Military Health System Phase I Report - Hepner, Kimberly A. (RAND Corporation, 2012)
Understanding the current quality of care for posttraumatic stress disorder (PTSD) and depression delivered to service members is an important step toward improving care across the Military Health System (MHS). T.his report describes the characteristics of active-component service members who received care for PTSD or depression through the MHS and assesses the quality of care received using quality measures derived from administrative data